Implementation of Tolerance Values ​​in Realizing Community Unity and Unity in Jayapura Village, Siak Regency - Anggi Subianto; Jumili Arianto; Sri Erlinda (CV. Rayyan Dwi Bharata, 2024)
The research was motivated by the many ethnicities, religions and cultures that exist in Jayapura village, Bungaraya sub-district, Siak district. The formulation of the problem in the research is how to implement the value of tolerance in realizing unity and integrity in Jayapura Village, Siak Regency, what are the forms of obstacles and efforts to implement the value of tolerance in social life in Jayapura Village. Meanwhile, the aim of this research is to determine the implementation of the value of tolerance and obstacles and efforts in social life in Jayapura Village. Data collection techniques are observation, interviews and documentation. There were 6 informants in this research, including the village head, youth leader, religious leader/community figure, teacher and local community. The data analysis technique in this research uses qualitative methods with a descriptive approach. The results of the research show that there is quite strong tolerance in respecting other people whose conditions are different, respecting other people, accepting differences, and not forcing others to be the same as themselves. Supporting factors for implementing the value of tolerance are the togetherness factor, an attitude of mutual help and support, community activities, and the heart factor. Then too, there are still inhibiting factors in the form of time and awareness from the community in Jayapura Village, Bungaraya District, Siak Regency.